Impulsivity and compulsivity as parallel mediators of emotion dysregulation in eating‐related addictive‐like behaviors, alcohol use, and compulsive exercise. Issue 1 (20th December 2021) - Forsén Mantilla, Emma; Clinton, David; Monell, Elin; Levallius, Johanna; Birgegård, Andreas
Abstract: Introduction: Transdiagnostically relevant psychological traits associated with psychiatric disorders are increasingly being researched, notably in substance use and addictive behaviors. We investigated whether emotion dysregulation mediated by impulsivity and/or compulsivity could explain variance in binge eating, food addiction, self‐starvation, and compulsive exercise, as well as alcohol use (addictive‐like behaviors relevant to the obesity and eating disorder fields). Method: A general population sample of adults ( N  = 500, mean age = 32.5 years), females ( n  = 376) and males ( n  = 124), completed the Difficulties in Emotion Regulation Scale‐16, the Trait Rash Impulsivity Scale, the Obsessive‐Compulsive Inventory—Revised, the Eating Disorders Examination Questionnaire, the Self‐Starvation Scale, the Exercise Dependence Scale, the Yale Food Addiction Scale, and the Alcohol Use Disorders Identification Test online. Besides gender comparisons and intercorrelations between measures, we used predefined multiple mediation models with emotion dysregulation as independent variable, impulsivity and compulsivity as parallel mediators, to investigate whether these factors contributed explanatory power to each addictive‐like behavior as outcome, also using age and body mass index as covariates. Results: Females scored higher than males on emotion dysregulation and the eating‐related addictive‐like behaviors food addiction, self‐starvation, and binge eating. Intercorrelations between measures showed that emotion dysregulation and compulsivity were associated with all outcome variables, impulsivity with all except compulsive exercise, and the eating‐related behaviors intercorrelated strongly. Mediation models showed full or partial mediation of emotion dysregulation for all behaviors, especially via compulsivity, suggesting a behavior‐specific pattern. Mediation models were not affected by age or gender. Discussion: Addictive‐like behaviors seemed to be maintained by trait levels of emotion dysregulation, albeit channeled via trait levels of compulsivity and/or impulsivity. The role of emotion dysregulation may help us to understand why addictive‐like behaviors can be difficult to change in both clinical and nonclinical groups, and may be informative for treatment‐planning in patients where these behaviors are present. Our findings support adopting a more dimensional approach to psychiatric classification by focusing psychological facets such as those studied. Abstract : We studied behaviors affecting weight, relevant for, for example, the obesity and the eating disorders fields, to investigate whether emotion dysregulation mediated by impulsivity and/or compulsivity could explain variance in binge eating, food addiction, self‐starvation, and compulsive exercise, as well as alcohol use. Mediation models showed full or partial mediation of emotion dysregulation for all behaviors, especially via compulsivity, in a suggestive disorder‐specific pattern.